(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Education is undergoing a transformation thanks to artificial intelligence (AI), which offers tailored learning experiences and improves skill development. The influence of AI on the development of writing abilities in language acquisition is examined in this essay. Through the use of AI-powered resources like grammar checkers, writing assistants, and personalized feedback systems, teachers may provide students with individualized teaching and assistance that leads to a considerable improvement in their writing skills. This essay examines the theoretical underpinnings of artificial intelligence (AI) in education, the advantages it offers for the improvement of writing abilities, and workable methods for incorporating AI into language training. We present case studies and in-depth analysis to show how AI may improve learners’ language competency in general and writing skills in particular.